1993
DOI: 10.1017/s0094837300015852
|View full text |Cite
|
Sign up to set email alerts
|

Numerical experiments with model monophyletic and paraphyletic taxa

Abstract: The problem of how accurately paraphyletic taxa versus monophyletic (i.e., holophyletic) groups (clades) capture underlying species patterns of diversity and extinction is explored with Monte Carlo simulations. Phylogenies are modeled as stochastic trees. Paraphyletic taxa are defined in an arbitrary manner by randomly choosing progenitors and clustering all descendants not belonging to other taxa. These taxa are then examined to determine which are clades, and the remaining paraphyletic groups are dissected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 42 publications
2
84
1
Order By: Relevance
“…Evidence for this global turnover is reflected by increased insect origination rates and, to a lesser extent, increased extinction rates demonstrated in family-level diversity studies (Labandeira & Sepkoski, 1993;Jarzembowski & Boss, 1996;Dmitriev & Ponomarenko, 2002;Labandeira, 2005b), as well as saturation of mouthpart disparity (Labandeira, 1997). In this context, Sepkoski and Kendrick (1993) have used model-based analyses to validate the use of taxic diversity data and methodology for understanding major macroevolutionary patterns (e.g., Crepet & Niklas, 2009).…”
Section: Mid Mesozoic Long-proboscid Insects and Their Seed Plant Hostsmentioning
confidence: 98%
See 1 more Smart Citation
“…Evidence for this global turnover is reflected by increased insect origination rates and, to a lesser extent, increased extinction rates demonstrated in family-level diversity studies (Labandeira & Sepkoski, 1993;Jarzembowski & Boss, 1996;Dmitriev & Ponomarenko, 2002;Labandeira, 2005b), as well as saturation of mouthpart disparity (Labandeira, 1997). In this context, Sepkoski and Kendrick (1993) have used model-based analyses to validate the use of taxic diversity data and methodology for understanding major macroevolutionary patterns (e.g., Crepet & Niklas, 2009).…”
Section: Mid Mesozoic Long-proboscid Insects and Their Seed Plant Hostsmentioning
confidence: 98%
“…An alternative explanation is that this plateau represents a lull in the recovery of insect taxa from earlier deposits with high numbers of insect species. Consequently, taxic data analyses can capture fossil insect diversity data (Sepkoski & Kendrick, 1993), indicating that global biotic changes resulted in major decreases in insect diversity. This diversity decrease is wedged between an earlier extinction episode and a subsequent diversification event in seed plants.…”
Section: The Impact Of Mid Mesozoic Pollination Data On Understandingmentioning
confidence: 99%
“…However, paraphyly is unlikely in itself to have artificially produced the results reported here. Regarding the genus-level analyses, numerical simulations have shown that paraphyly is unlikely to mask or generate major patterns of taxonomic origination and extinction, especially given the large number of taxa involved (27)(28)(29)(30)(31)(32). Order-level systematics have been increasingly cast in cladistic terms [e.g., echinoderms (33), trilobites (34), and brachiopods (35)].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Order-level systematics have been increasingly cast in cladistic terms [e.g., echinoderms (33), trilobites (34), and brachiopods (35)]. Extinct orders that have not been revised from this standpoint probably represent true termination of constituent lineages in most instances, either owing to strict monophyly or because paraclades were split significantly before the last appearance of the ordinal taxon, so that the loss of that taxon is meaningful in terms of biodiversity (27)(28)(29). Extensive ''pseudoextinction'' of orders at or immediately following extinction boundaries is thus unlikely.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Sepkoski & Kendrick 1993;Robeck et al 2000). These studies focus on synoptic databases of first and last appearances (e.g.…”
Section: Introductionmentioning
confidence: 99%